THE MODEL OF INTERNAL FINANCE CONTROL IN A BUDGET SECTOR AS A BASIS OF THE SYSTEM OF STATE FINANCE CONTROL OF THE ENTITY OF THE RUSSIAN FEDERATION - Olga I. Usenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article discusses issues of interconnection between internal finance control of budget sector participants and the system of state (municipal) finance control, analyzes legal and methodological support of internal finance control in the budget sector, systematizes the key problems of internal finance control. The author proposes the algorithm of organizing internal finance control in the budget sector in the entity of the Russian Federation, methodology of identifying the way to organize internal finance control in the budget sector at the regional level and methodology of analyzing finance support of finance control in the budget sector at the regional level.